Clinical and biochemical determinants of length of stay, readmission and recurrence in patients admitted with diabetic ketoacidosis. (31st December 2023) - Ata, Fateen; Khan, Adeel Ahmad; Khamees, Ibrahim; Iqbal, Phool; Yousaf, Zohaib; Mohammed, Bayan Z. M.; Aboshdid, Reham; Marzouk, Sandy K. K.; Barjas, Haidar; Khalid, Madiha; El Madhoun, Ihab; Bashir, Mohammed; et al.
Abstract: Background: The increasing prevalence of diabetic ketoacidosis (DKA) related admissions poses a significant burden on the healthcare systems globally. However, data regarding the predictors of healthcare resource utilization in DKA is limited and inconsistent. This study aimed to identify key predictors of hospital length of stay (LOS), readmission and recurrent DKA episodes. Methods: We undertook a retrospective cross-sectional analysis of all DKA admissions from 2015 to 2021 across four hospitals in Qatar. The primary outcomes were the length of stay (LOS), 90-day readmission and 6-month and 1-year DKA recurrence. Results: We included 922 patients with a median age of 35 years (25–45). 62% were males with type-1 diabetes-mellitus (T1DM) and type-2 DM (T2DM), present in 52% and 48% of patients. The median LOS was 2.6 days (IQR 1.1–4.8), and the median DKA resolution time was 18 h (10.5–29). Male-gender, new-onset DM, higher Charlson Comorbidity Index (CCI), lower haemoglobin, sodium and potassium, higher urea, longer DKA duration and MICU admission predicted a longer LOS in a multivariate regression analysis. None of the factors were significantly associated with 90-day readmission. Patients with pre-existing T1DM were more likely to have a six-month DKA recurrence than pre-existing T2DM. Patients with a 6-month DKA recurrence, female gender and T1DM had higher odds of 12-month recurrence, whereas a consult with a diabetes educator at the index admission was associated with decreased odds of recurrence. Conclusions/interpretation: This is the most extensive study from the Middle-East region reporting on LOS, readmissions and the recurrence of DKA. Results from this study with a diverse population may be valuable for physicians and healthcare systems to decrease the diabetes-related healthcare burden in DKA patients. Graphical Abstract: UF0001 Key Messages: This study showed that the hospital length of stay and recurrent episodes can be predicted in patients with diabetic ketoacidosis (DKA). Multimorbidity, male gender, newly developed T2DM, anaemia, hyponatremia, hypokalaemia, high urea levels and intensive care can predict LOS in DKA patients. DKA recurrence at 6 and 12 months is higher in females, younger age, non-obese patients, poor insulin compliance and in pre-existing T1DM.